2022
DOI: 10.1159/000524282
|View full text |Cite
|
Sign up to set email alerts
|

Specific Alterations of Gut Microbiota in Chinese Patients with Hypertension: A Systematic Review and Meta-Analysis

Abstract: Background: China has the largest absolute burden of hypertension (HTN) in the world. Gut dysbiosis may be a potentially modifiable risk factor for HTN. However, the characteristics of gut microbiota in Chinese populations with HTN remain to be determined. Methods: We systematically searched for studies comparing the gut microbial in HTN with healthy controls in databases. The cut-off date was December 30, 2021. Semiquantitative analysis and meta-analysis with standardized mean differences of the alteration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…In this study, the Shannon index of hypertensive patients decreased significantly, which was partially consistent with the results of Yang and coworkers 47 The difference was that there was no significant difference in Chao1 index between HTN and HC in this study. This result suggested that although the diversity of GM in hypertensive patients had been damaged to some extent, the richness had been retained as a whole 21 . In addition, we also found that there was a negative correlation between the Shannon index and HTN, which was consistent with the reported significant decrease in the Shannon index of GM in hypertensive patients in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the Shannon index of hypertensive patients decreased significantly, which was partially consistent with the results of Yang and coworkers 47 The difference was that there was no significant difference in Chao1 index between HTN and HC in this study. This result suggested that although the diversity of GM in hypertensive patients had been damaged to some extent, the richness had been retained as a whole 21 . In addition, we also found that there was a negative correlation between the Shannon index and HTN, which was consistent with the reported significant decrease in the Shannon index of GM in hypertensive patients in this study.…”
Section: Discussionsupporting
confidence: 90%
“…It is worth noting that although this study conducted meta‐analysis on gut microbial diversity indicators such as Shannon, Simpson, Chao1, ACE, the relative abundance of microbial groups was only semi‐quantitatively analyzed, and no combined analysis was conducted on them. In addition, due to the insufficient measurement depth and differences in measurement methods of the microbiome in the included studies, there was still no clear evidence to identify pathogenic bacteria closely related to HTN 21 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, a previous study on animals reported that a fecal microbiota transplant from hypertensive mice into germ-free mice resulted in the animals developing hypertension [ 37 ]. In addition, several studies have reported an association between hypertension and dysbiosis, indicating that the intestinal bacterial equilibrium plays an important role in the development of hypertension and in blood pressure control [ 38 , 39 ]. Consistent with the findings of these studies, the non-responders in this study tended to have a lower Shannon index, which was calculated based on the proportion of species in a gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…In a healthy intestinal ecosystem, Bacteroidetes and Firmicutes are the dominant bacterial groups, and thus, the Firmicutes/Bacteroidetes (F/B) ratio can be regarded as a potential biomarker for pathological states. 13 A study based on high-throughput sequencing technology using fecal samples from patients with grade 3 hypertension and healthy controls revealed that the gut microbiota of hypertensive patients exhibited significant decreases in abundance, diversity, and uniformity, with a notable increase in the F/B ratio. This increase was accompanied by an elevation in the abundance of Prevotella_9, Megasphaera, Parasutterella, and Escherichia Shigella, while the abundance of Bacteroides and Faecalibacterium decreased.…”
Section: Different Gut Microbiota and Hypertensionmentioning
confidence: 99%